Peningkatan Efisiensi Dan Kualitas di Politeknik Negeri Medan Melalui Pengembangan Sistem Informasi Akademik dan Repository Perpustakaan - Agus Edy Rangkuti; Ferry Fachrizal (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2024)
This study aims to develop an academic correspondence application within the student grade portal of Politeknik Negeri Medan and establish a repository in the institution's library. The benefits of this research include: 1) Enhancing Efficiency and Quality of Academic Services: The implementation of an online academic correspondence application enables the institution to improve administrative efficiency, reduce recording errors, and ensure more responsive and high-quality services for students and academic staff. 2) Improving Accessibility and Scientific Contribution: The library repository facilitates access to scientific works such as theses, journals, and faculty research. This supports learning and research activities while increasing the visibility and contribution of Politeknik Negeri Medan within the academic community. The research findings demonstrate the following outcomes: 1) Development of the Academic Correspondence Application: The application successfully provides an efficient solution to address various academic administration challenges, such as slow submission processes and lack of transparency. It enhances process speed, minimizes administrative errors, and improves the user experience for students and administrative staff. 2) Establishment of a DSpace-Based Library Repository: The repository offers a reliable digital platform for storing, managing, and accessing academic collections. It has effectively improved information accessibility, document management efficiency, and institutional visibility within the academic community.